Biomarkers of Suture Density and Thickness in Craniofacial Bone Growth: Micro-CT Analysis - Wahyuni Dyah Parmasari; I Gusti Aju Wahju Ardani; Ida Bagus Narmada; Alexander Patera Nugraha; Ramadhan Hardani Putra; Fourier Dzar Eljabbar Latief; Fahrisah Nurfadeliah Bahraini (Fakultas Kedokteran Gigi, Universitas Mahasaraswati Denpasar, 2025)
Introduction: One of the parameters for measuring craniofacial growth is suture closure. The sutures are connected with fibrous connective tissue that grows in a few days. The objective is to analyze the gray-scale value (GV) potential by measuring the volume of interest (VOI) of the different skulls using micro-computed tomography (Micro-CT). The analysis uses certain parameters, namely density and thickness. Material and Methods: This study involves experimental mice to examine normal growth and development processes at a certain age by investigating mice’s suture maturation. If the suture closure process has been completed, it can be used as a potential standard for measuring the cessation of growth in the craniofacial area. This study examined three different skulls obtained from 15-day-old (cranium 1) baby mice, 25-day-old (cranium 2) baby mice, and 120-day-old adult mice (cranium 3). The possible GV was 0 to 255 (Micro-CT-reconstructed image dataset in 8-bit-BMP-format). There was a volumetric space that limited the analysis area of the bone tissue whose density was measured. In micro-CT-reconstructed images, VOI was determined by the region-of-interest (ROI) in the 2D image slices, which completely formed an image. The machine used was a Bruker SkyScan 1173 high energy micro-CT. Results and Discussions: The suture of Cranium 1, Cranium 2, and Cranium 3 have a relative mean density (GV) of 32,45; 29,74; and 50,1, respectively. This study also measures the geometric average measurement of bone cranium thickness with a 5x5 mm cross-section. The average thickness of cranium 1 is 0.554 mm, cranium 2 is 0.645 mm, and cranium 3 is 1.417 mm. Conclusion: Sutures cranium 1 and 2 are lower in density and thinner than cranium 3 as documented by means of Micro-CT.